A patterned ceramic film tape of multiple host crystal phases and a method of manufacturing the same
Patent Information
- Application Number
- CN202611121154.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-27
- Publication Date
- 2026-10-16
AI Technical Summary
[0005]本发明针对现有陶瓷膜带制备技术中难以在同一平面内实现多种不同主晶相陶瓷材料异质集成共烧、以及缺乏面向集成电路局域化点对点制冷的陶瓷基功能单元等问题,制备了一种多主晶相的图形化陶瓷膜带
本发明提供了一种可以在面内实现异质陶瓷共面共烧集成的方法,与单一主晶相流延为主制备陶瓷膜带相比,异质结构仅局限于金属-陶瓷异质共烧或层间叠层共烧,本发明通过分步流延结合定制模板图形化填充的方法,首次实现了在同一平面内多种不同主晶相陶瓷材料的图形化集成与一次共烧成型,使传统的叠层工艺方法向平面工艺延伸,填补了面内异质集成共烧的技术空白。
Smart Images

Figure CN122916652A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of ceramic materials and their preparation technology, specifically relating to a patterned ceramic film strip with multiple principal phases and its preparation method. This invention is particularly applicable to localized point-to-point heat dissipation devices in the field of integrated circuits, and can also be used in the manufacture of multifunctional ceramic devices and structural ceramic devices. Background Technology
[0002] With the advancement of process node miniaturization, high-density integration, and three-dimensional packaging architecture, chip heat flux density is increasing exponentially. The heat dissipation capabilities of traditional passive cooling technologies such as air cooling, liquid cooling, and microfluidic systems are gradually approaching their theoretical limits and engineering application boundaries. High temperatures not only affect the lifespan and operational reliability of chips but also directly restrict chip performance release through mechanisms such as triggering frequency derating, power limiting, and uncontrolled local hotspots. Therefore, improving heat dissipation capabilities is no longer simply a matter of reliability assurance but a key constraint determining the feasibility of advanced integrated circuit technology development paths. In recent years, card cooling has become a research hotspot for solving the heat dissipation problem of high-density integrated circuits due to its high efficiency, high power, long lifespan, and ease of miniaturization. However, this technology is in its early stages of engineering, and existing research is mostly limited to large-space scenarios such as air conditioners and battery packs. When applied to integrated circuit heat dissipation, it still cannot meet the requirements for precise local cooling and long-term reliable operation under non-uniform distribution of chip heat sources.
[0003] Ceramic tapes are a key physical carrier connecting the heat dissipation requirements of high-density integrated circuits and electro-cooling technology. Currently, ceramic tapes are typically fabricated using a single main crystalline phase slurry casting method. While this method is easy to implement in continuous production and offers high product consistency and yield, it lacks process flexibility and limits material integration capabilities. Regarding heterogeneous material integration, existing technologies mainly focus on the co-firing of metals and ceramics for internal electrodes and wiring layers, as well as the co-firing of stacked layers of different materials. However, no mature technical solution has yet been proposed for the heterogeneous integration and co-firing of multiple different ceramic materials within the same plane. For example, Chinese patent application CN201910222477.7 discloses a method for manufacturing a low-temperature co-fired ceramic circuit board. Before stacking the low-temperature co-fired ceramic green sheets after conductor printing, the method performs a hot-pressing pretreatment on the green sheets to modify the surface morphology of the through-hole paste, thereby filling the through-hole paste densely, improving the diffusion degree of the paste between layers, preventing micro-cracks at the interlayer interface of the low-temperature co-fired ceramic circuit board, and ensuring the reliability of the circuit board. However, this method addresses the reliability problem of the interlayer interface during the stacked ceramic co-firing process, which belongs to vertical heterogeneous integration and does not involve the same... A technical solution for integrating multiple ceramic materials with different main crystal phases in a plane; Chinese patent application CN202610187326.2 discloses a method for manufacturing a low-cost semiconductor cooler. Although this method reduces the manufacturing cost of semiconductor coolers and simplifies the process flow, and proposes the concept of a patterned array, the ceramic substrate used is a single main crystal phase material, and different functional areas are achieved by evaporating different metal electrodes. It does not involve a technical solution for integrating multiple ceramic materials with different main crystal phases in the same ceramic substrate, nor can it achieve localized cooling control based on the performance differences of different ferroelectric ceramic materials.
[0004] Therefore, existing technologies lack a technique capable of patterned integration of multiple main crystalline phase ceramic materials within the same plane and applicable to localized point-to-point cooling of integrated circuits. To address these technical problems, this invention proposes a patterned ceramic film strip with multiple main crystalline phases and its preparation method. Summary of the Invention
[0005] This invention addresses the problems in existing ceramic film and tape fabrication technologies, such as the difficulty in achieving heterogeneous integration and co-firing of multiple main crystalline phase ceramic materials in the same plane and the lack of ceramic-based functional units for localized point-to-point cooling of integrated circuits. It prepares a patterned ceramic film and tape with multiple main crystalline phases.
[0006] This invention aims to solve the technical problem in the prior art where the preparation of ceramic film tapes is mainly based on the casting of a single main crystal phase and heterogeneous integration is limited to metal-ceramic co-firing or interlayer stacking co-firing, which makes it impossible to achieve regional integration of multiple different functional ceramic materials in a single plane, and thus makes it difficult to meet the requirements of localized, point-to-point efficient cooling under the non-uniform heat source distribution of integrated circuits.
[0007] To achieve the above objectives, the present invention provides the following technical solution: In a first aspect, the present invention provides a patterned ceramic film strip with multiple main crystal phases, wherein the ceramic film strip contains material regions of at least two different main crystal phases in the same plane, the material regions are distributed in a preset patterned array, and the material regions of different main crystal phases are seamlessly bonded together by co-firing.
[0008] Preferably, the surface of the ceramic film strip is further provided with an electrode layer, which enables in-plane electrical interconnection between different main crystalline phase material regions.
[0009] Preferably, the main crystalline phase is selected from one or more of barium titanate, lead zirconate titanate, sodium bismuth titanate, and their mixed dopants.
[0010] Secondly, the present invention also provides a method for preparing the above-mentioned patterned ceramic film strip with multiple principal phases, comprising the following steps: (1) Raw material preparation At least two different main crystalline phases of ceramic powder and glass powder with a glass transition temperature between 500℃ and 950℃ are selected respectively; the glass powder and the lower limit of the sintering window of each main crystalline phase material are not more than 50℃ apart. (2) Preparation of casting slurry Each main crystalline phase ceramic powder is mixed with glass powder, binder, dispersant, plasticizer and organic solvent to prepare first main crystalline phase casting slurry, second main crystalline phase casting slurry and more casting slurries with different main crystalline phases respectively. The mass ratio of binder, dispersant, plasticizer and organic solvent is (0.1~0.2):1:1:(0.05~0.15); (3) Step-by-step casting The process is carried out in steps. First, the first main crystalline phase slurry is formed by conventional tape casting process to make a thick film green film of the first main crystalline phase system. By using a customized template to press-cut or punch holes in the thick film green film of the first main crystalline phase system, at least one patterned opening region is formed, thereby obtaining a patterned green film strip of the first main crystalline phase. A customized flexible graphic template is aligned and covered on the first main crystal phase patterned green film strip. The second main crystal phase casting slurry is used to perform a second casting process, so that the second main crystal phase casting slurry fills the patterned opening area to obtain a composite green film strip containing two different main crystal phase material regions. If a third or more different main crystalline phase materials are to be introduced, repeat the above steps and fill the corresponding patterned areas with the subsequent main crystalline phase casting paste in sequence. (4) Electrode pattern printing Using screen printing technology with nickel or silver as electrode materials, electrode patterns are printed on the surface of the composite green film strip using a customized mask to achieve in-plane electrical interconnection between regions of different main crystalline phase materials. (5) Press bonding The composite green film strip printed with electrode patterns is subjected to warm isostatic pressing to enhance the green bonding between different pattern areas. (6) De-glue The composite green film strip after being subjected to isostatic pressing was placed in a muffle furnace and heated in sections within the temperature range of 120℃ to 380℃ for 30 to 40 hours to produce a pre-fired ceramic green film. (7) Sintering The pre-fired ceramic green body is transferred to a high-temperature muffle furnace or atmosphere furnace and sintered at 1000℃~1450℃ for 4~10 h in a reducing atmosphere to obtain the patterned ceramic film strip with multiple principal crystalline phases.
[0011] Preferably, in step 1, the glass powder is selected from one or more of the following: alkaline earth borosilicate glass SiO2-B2O3-Al2O3-RO (R=Ca, Mg, Sr, Ba), high borosilicate glass SiO2 (~80%)-B2O3 (~13%)-Na2O / Al2O3, CaO-B2O3-SiO2, or lead-free borosilicate glass SiO2-B2O3-AlF3-SrO.
[0012] Preferably, in step (1), the main crystalline phase ceramic powder is selected from one or more of barium titanate, lead zirconate titanate, sodium bismuth titanate, and their mixed dopants.
[0013] Preferably, in step (2), the binder is polyvinyl butyral (PVB) or polyvinyl alcohol (PVA); the dispersant is toluene, phosphate ester, fresh fish oil or ethyl cellulose; the plasticizer is diisobutyl phthalate, polyethylene glycol or ethylene glycol; and the organic solvent is ethanol, toluene or xylene.
[0014] Preferably, the patterning process in step (3) includes: using a customized template to press-cut or punch the first ceramic green film strip to form an opening, through hole or groove as the patterned area.
[0015] Preferably, the above preparation method further includes repeating steps S2 to S4 at least once after step (4) to introduce patterned regions of a third or more different main crystal phases.
[0016] Preferably, after step (4) and before step (5), the method further includes: printing electrode patterns on the composite green film strip, and printing electrode materials on the surface of the composite green film strip using screen printing technology to form in-plane electrical interconnection.
[0017] Preferably, after step (4) and before step (5), the composite green film strip is subjected to isostatic pressing to enhance the green bonding between different main crystal phase pattern regions.
[0018] Specifically, the isostatic pressing treatment is performed at a temperature of 50℃ to 150℃, a pressure of 10MPa to 50MPa, and a treatment time of 5 to 30 minutes.
[0019] Preferably, the casting slurry comprises a main crystalline phase powder, a glass powder, a binder, a dispersant, a plasticizer, and an organic solvent; the glass transition temperature of the glass powder is 500 ℃ to 950 ℃, and the difference between the glass powder and the lower limit of the sintering window of the main crystalline phase material does not exceed 50 ℃.
[0020] Preferably, the debinding process is performed by heating in sections within a temperature range of 120 ℃ to 380 ℃ for 30 to 40 h; the sintering process is performed by sintering at a temperature of 1000 ℃ to 1450 ℃ for 4 to 10 h in a reducing atmosphere.
[0021] Specifically, the reducing atmosphere is achieved by controlling the partial pressure of the H2 / O2 mixture in the sintering furnace.
[0022] Thirdly, the present invention also provides the application of the above-mentioned patterned ceramic film strip with multiple main crystal phases or the above-mentioned preparation method in localized point-to-point cooling of integrated circuits.
[0023] Compared with the prior art, the present invention has the following beneficial effects: This invention provides a method for achieving in-plane co-firing integration of heterogeneous ceramics. Compared with the preparation of ceramic films mainly by single main crystalline phase tape casting, heterogeneous structures are limited to metal-ceramic heterogeneous co-firing or interlayer stacking co-firing. This invention, through step-by-step tape casting combined with customized template patterned filling, achieves for the first time the patterned integration and one-time co-firing of multiple ceramic materials with different main crystalline phases in the same plane, extending the traditional stacking process to planar processes and filling the technical gap of in-plane heterogeneous integration co-firing.
[0024] This invention can be used to fabricate array-type, customized, and patterned functional ceramic structures, achieving the integration of multiple functions within the same plane through in-plane circuit design. Different main crystalline phase material regions can be customized with patterned designs according to actual needs, such as checkerboard, honeycomb, or concentric ring arrays, and in-plane electrical interconnection is achieved through printed electrodes, providing technical guidance for the multifunctional coupling and integration of functional ceramics.
[0025] This invention effectively realizes localized, point-to-point cooling functions based on ferroelectric ceramics to meet the engineering needs of integrated circuits. By graphically integrating ferroelectric ceramic materials such as barium titanate, lead zirconate titanate, and sodium bismuth titanate with different Curie points or electrocaloric properties according to the hot spot distribution of the chip, differentiated and localized active cooling can be performed on different areas of the chip. This overcomes the shortcomings of traditional passive heat dissipation technology, which cannot achieve precise local cooling, and provides a brand-new solution for thermal management of high-density integrated circuits.
[0026] The preparation method of the present invention has good process scalability and is not only applicable to the ceramic functional unit of electric card refrigeration, but can also be extended to the preparation of functional ceramic devices such as piezoelectric sensors, dielectric capacitors, and ferroelectric memory, as well as structural ceramic devices such as composite ceramic cutting tools with wear-resistant and tough regions, and has broad application prospects. Attached Figure Description
[0027] To more clearly illustrate the technical solution of the present invention, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0028] Figure 1 This is a flowchart of the preparation process in an embodiment of the present invention.
[0029] Figure 2 The diagram shows the microstructure, elemental distribution, and dielectric properties of the ceramic film strip in Example 1 of this invention. Detailed Implementation
[0030] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to specific examples. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0031] Unless otherwise specified, the experimental methods used in this invention are conventional methods; unless otherwise specified, the materials and reagents used are commercially available.
[0032] In this invention, the term "single main phase slurry casting" refers to the process of first mixing a certain ceramic powder with solvent, dispersant, binder, plasticizer, etc. to prepare a casting slurry, then preparing a homogeneous ceramic green film through a casting process, and subsequently forming a device structure through punching, stacking, printing, filling or sintering.
[0033] In this invention, the term "ceramic film tape" refers to ceramic sheets or substrates obtained by casting, debinding, and sintering, which may be in a green state or a sintered state.
[0034] Example 1 A patterned ceramic film with multiple principal phases and its preparation method, such as Figure 1 As shown, it includes the following steps: Step 1: Raw material preparation Main crystalline phase 1: Barium titanate (BaTiO3, BTO) powder, with an average particle size of 0.8 μm and a purity of ≥99.9%.
[0035] Main crystal phase 2: Lead zirconate titanate (Ba 0.7 Sr 0.3 TiO3 (BST) powder, with an average particle size of 0.6 μm and a purity of ≥99.9%.
[0036] Glass powder: aluminosilicate glass with a glass transition temperature of 600℃, which is about 30℃ different from the lower limit of the sintering window of the main crystalline phase.
[0037] Step 2: Preparation of Casting Slurry Main crystalline phase 1 and main crystalline phase 2 were respectively mixed with glass powder, binder (polyvinyl butyral, PVB), dispersant (toluene), plasticizer (diisobutyl phthalate), and organic solvent (prepared by mixing anhydrous ethanol and toluene in a volume ratio of 1:1). The mass ratio of binder, dispersant, plasticizer, and organic solvent was 0.15:1:1:0.10. The mixtures were ball-milled at 300 rpm for 8 h and then degassed under vacuum for 20 min to obtain the first and second main crystalline phase casting slurries, respectively.
[0038] Step 3: Step-by-step casting The first main crystalline phase slurry was cast using a casting machine with a doctor blade gap of 100 μm and a casting speed of 0.5 m / min to obtain a thick film green film of the first main crystalline phase with a thickness of about 80 μm.
[0039] The green embryo is cut using a custom stainless steel template to form a square array of through holes with a side length of 1 mm and a spacing of 3 mm (center distance), thus obtaining a patterned green embryo membrane strip.
[0040] A flexible polyester graphic template is applied to the above-mentioned film strip, and a second casting is performed using a second main crystalline phase casting slurry. The doctor blade gap is set to 150 μm to ensure that the slurry fully fills the through-holes, thereby obtaining a composite green film strip.
[0041] Step 4: Electrode Pattern Printing Interdigitated electrode patterns were printed onto the surface of a composite green film using a screen printing process with nickel paste as the electrode material and a custom mask. The electrode linewidth was 100 μm and the electrode spacing was 150 μm. After printing, the film was dried at 80 °C for 30 min to achieve in-plane electrical interconnection.
[0042] Step 5: Pressing and bonding The printed composite green film tape is subjected to isostatic pressing treatment at a temperature of 80℃, a pressure of 30MPa, and a holding time of 15min.
[0043] Step 6: Remove glue The pressed green film was placed in a muffle furnace and the binder was removed according to the following procedure: at room temperature, the temperature was increased to 120 ℃ at 1 ℃ / min and held at 120 ℃ for 2 h; then the temperature was increased to 250 ℃ at 0.8 ℃ / min and held at 250 ℃ for 4 h; then the temperature was increased to 380 ℃ at 0.5 ℃ / min and held at 380 ℃ for 6 h; and then the film was allowed to cool naturally to room temperature. The total binder removal time was about 36 h, and the pre-fired ceramic green film was obtained.
[0044] Step 7: Sintering The pre-fired ceramic green body was transferred to an atmosphere furnace and heated to 1300 °C at a rate of 5 °C / min under a reducing atmosphere (H2 / N2 mixture, H2 volume fraction 2%), held for 6 h, and then cooled with the furnace to obtain a multi-principal phase patterned ceramic film. The thickness of the film after sintering was approximately 150 μm.
[0045] Example 2 The difference between Example 2 and Example 1 is that: Main phase 2 is replaced with sodium bismuth titanate (Bi 0.5 Na 0.5 TiO3, NBT powder, with an average particle size of 0.7 μm.
[0046] The shape of the patterned array was changed to a square through hole with a side length of 300 μm × 300 μm and a hole spacing of 1.0 mm.
[0047] The electrode material was changed to nickel paste (70wt% nickel content).
[0048] The sintering temperature was adjusted to 1150℃.
[0049] The remaining steps and parameters are the same as in Example 1.
[0050] Example 3 The difference between Example 3 and Example 1 is that: Introducing main crystalline phase 3: lanthanum-doped barium titanate (Ba 0.8 La 0.2 TiO3 (BLT) powder with an average particle size of 0.8 μm.
[0051] The graphical layout is a concentric circle structure: the central circular area is filled with BST (600 μm in diameter), the annular middle area is filled with BLT (600 μm inner diameter, 1200 μm outer diameter), and the outer area is filled with barium titanate. The filling is performed in three steps using a sequential casting process.
[0052] The electrode pattern is designed as three sets of independent interdigitated electrodes, each controlling one of the three regions.
[0053] The remaining steps and parameters are the same as in Example 1.
[0054] Comparative Example 1 Comparative Example 1 provides a method for preparing a single main crystalline phase ceramic film strip, specifically as follows: Using the same barium titanate powder, glass powder, binder, plasticizer, and solvent ratio as in Example 1, a single-phase casting slurry was prepared. After a single casting process, with a green thickness of 200 μm, warm isostatic pressing (80℃, 30 MPa, 15 min), binder removal, and sintering as in Example 1, a single-phase ceramic film was obtained. No patterning or second casting filling was performed.
[0055] Comparative Example 2 Comparative Example 2 uses a layered co-firing method to prepare two main crystalline phase layered ceramics, specifically: The preparation of barium titanate and lead zirconate titanate casting slurries was the same as in Example 1, and they were then cast into single-layer films (each layer approximately 150 μm thick). These films were then stacked in the order of barium titanate layer / BST layer / barium titanate layer, and subjected to warm isostatic pressing, binder removal, and sintering as in Example 1 to obtain a three-layer stacked heterogeneous ceramic. This structure exhibits different principal crystalline phases in the thickness direction, but is homogeneous within the same plane.
[0056] Comparative Example 3 Comparative Example 3 uses a method of combining a single main phase ceramic substrate with surface-deposited metal patterns.
[0057] Commercially available barium titanate sintered substrate (200 μm thick, 50 mm × 50 mm in size) was used, and interdigitated metal electrode patterns (100 μm line width, 150 μm spacing, and silver material) were formed on the surface by electron beam evaporation.
[0058] In this comparative example, multi-principal phase integration is not performed.
[0059] Test Example 1 I. Microstructure and interface bonding.
[0060] Test method: The cross-section and planar interface region of the ceramic film strips in Examples 1-3 and Comparative Examples 1-2 were observed using a scanning electron microscope (SEM) with an accelerating voltage of 15 kV and a magnification of 500-5000 times.
[0061] Table 1. Microstructure and Interface Bonding II. Compositional Distribution in Different Principal Crystal Phase Regions Test method: Energy dispersive spectroscopy (EDS) was used to perform line scanning on the interface region of Example 1 to detect the distribution of elements such as Ba and Sr.
[0062] III. Results Analysis like Figure 2 As shown, the ceramic film tape prepared in Example 1 achieved a gradient connection between BTO and BST through sintering, and the gradient distribution of Sr successfully controlled the Curie temperature from 120°C (pure BTO) to near room temperature (BST), thus realizing a gradient change in dielectric properties.
[0063] Meanwhile, the elemental distribution test results show that different ceramic composition regions have clear compositional boundaries and good distinguishability in the plane; the dielectric property test results further show that the electrical response in the preset functional areas exhibits significant differences, indicating that the step-by-step casting, patterning, and co-firing processes can achieve controllable construction of different functional ceramic regions in the same ceramic substrate plane.
[0064] Test Example 2 Dielectric property testing.
[0065] Test methods: The dielectric constant and dielectric loss of different regions of each sample were measured using a precision impedance analyzer at room temperature (25°C) and 1 kHz. Examples 1-3 used microprobes to test different patterned regions, Comparative Example 1 tested the entire sample, Comparative Example 2 tested the top and bottom layers respectively, and Comparative Example 3 tested the entire substrate.
[0066] Table 2 Dielectric performance test results As shown in Table 2, compared with Comparative Examples 1-3, the dielectric constant and dielectric loss of each main crystal phase region in Examples 1-3 are basically consistent with the measured values of the corresponding single-phase materials, with a deviation within ±2%. This indicates that the step-by-step casting and co-firing process did not significantly degrade the intrinsic dielectric properties of the material, and the dielectric characteristics of different main crystal phase regions were maintained.
[0067] Test Example 3 Electrocaloric effect cooling performance test.
[0068] Test Method: A periodic electric field (10 kV / cm, 1 Hz, square wave) was applied to the surface of the ceramic film strips in Examples 1-3 and Comparative Examples 1-3. An infrared thermal imager (resolution 0.05 °C) was used to measure the steady-state cooling temperature difference (ΔT, i.e., the maximum temperature drop relative to the initial temperature after applying the electric field) of each region's surface. For Example 3, the independent temperature drop in the center, ring area, and outer perimeter areas was measured respectively. The ambient temperature was set to 25 °C. The test results are shown in Table 3 below: Table 3. Test Results of Refrigeration Performance Due to Electrocaloric Effect Test column 4 Thermal stability and cycle life testing Test method: The ceramic membrane strip of Example 1 was aged in air at 150°C for 100 h, and then the electrocaloric cooling test was repeated at room temperature (under the same conditions as in Test Example 4), and the cooling temperature difference before and after aging was recorded; another sample was continuously cycled for 10 hours at 10 kV / cm and 1 Hz. 6 After the test, observe whether cracks appear on the interface and measure the cooling temperature difference.
[0069] Test results: After aging for 100 hours, the temperature difference attenuation rate in the barium titanate region was ≤5% (from -2.8℃ to -2.66℃), and the attenuation rate in the BST region was ≤4% (from -3.5℃ to -3.36℃). No new cracks were found at the interface.
[0070] 10 6 After each electrical cycle, the refrigeration temperature difference attenuation rate was ≤8%, and SEM observation showed that the interface bonding remained good, with no delamination or obvious fatigue cracks. This indicates that the product of this invention has good long-term thermal stability and electrical cycle reliability.
[0071] Test Example 5 In-plane electrical interconnection resistance test.
[0072] Test method: The sheet resistance of the printed electrodes in Examples 1-3 and the series resistance between adjacent main crystal phase regions connected by electrodes were measured using the four-probe method.
[0073] Table 4. Test Results of In-Plane Electrical Interconnection Resistance As shown in Table 4, the electrode resistance of the multi-principal phase patterned ceramic film strip of the present invention is low, which can meet the driving requirements of the card cooling unit in the integrated circuit.
[0074] In summary, the multi-principal phase patterned ceramic film strip provided by this invention, through step-by-step casting combined with patterned template filling and co-firing processes, successfully achieves patterned integration of multiple different principal phase ceramic materials in the same plane. The prepared ceramic film strip has good interfacial bonding between different regions, each maintaining excellent intrinsic dielectric properties and electrocardiographic effect, and can achieve in-plane differentiated local cooling, providing a practical and feasible technical solution for point-to-point active heat dissipation of non-uniform heat sources in integrated circuits.
[0075] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.
Claims
1. A patterned ceramic film strip with multiple principal phases, characterized in that, The ceramic film strip contains material regions of at least two different main crystalline phases in the same plane. The material regions are distributed in a preset patterned array, and the material regions of different main crystalline phases are seamlessly bonded together through co-firing.
2. The patterned ceramic film strip with multiple principal phases according to claim 1, characterized in that, The surface of the ceramic film strip is also provided with an electrode layer, which enables in-plane electrical interconnection between different main crystalline phase material regions.
3. The patterned ceramic film strip with multiple principal phases according to claim 1, characterized in that, The main crystalline phase is selected from one or more of barium titanate, lead zirconate titanate, sodium bismuth titanate, and their mixed dopants.
4. A method for preparing a patterned ceramic film strip with multiple principal phases as described in any one of claims 1-3, characterized in that, Includes the following steps: (1) Prepare at least two different main crystalline phases of casting paste, including a first main crystalline phase casting paste and a second main crystalline phase casting paste; (2) The first main crystal phase casting slurry is cast for the first time to obtain the first ceramic green film strip; (3) The first ceramic green film strip is patterned to form at least one patterned region; (4) The second main crystalline phase casting slurry is filled into the patterned area and a second casting is performed to obtain a composite green film belt containing at least two different main crystalline phase material regions; (5) The composite green film belt is subjected to debinding and sintering treatment in sequence to obtain the patterned ceramic film belt with multiple main crystal phases.
5. The preparation method according to claim 4, characterized in that, The patterning process in step (3) includes: using a customized template to press-cut or punch the first ceramic green film strip to form an opening, through hole or groove as the patterned area.
6. The preparation method according to claim 4, characterized in that, Also includes: After step (4), steps S2 to S4 are repeated at least once to introduce patterned regions of a third or more different main crystalline phases.
7. The preparation method according to claim 4, characterized in that, After step (4) and before step S5, the method further includes: printing electrode patterns on the composite green film strip, and printing electrode materials on the surface of the composite green film strip using screen printing technology to form in-plane electrical interconnection.
8. The preparation method according to claim 4, characterized in that, After step (4) and before step (5), the method further includes: performing isostatic pressing on the composite green film strip to enhance the green bonding between different main crystal phase pattern regions.
9. The preparation method according to claim 4, characterized in that, The casting slurry comprises a main crystalline phase powder, glass powder, binder, dispersant, plasticizer, and organic solvent; the glass transition temperature of the glass powder is 500℃~950℃, and the difference between it and the lower limit of the sintering window of the main crystalline phase material does not exceed 50℃.
10. The preparation method according to claim 4, characterized in that, The debinding process involves segmented heating within a temperature range of 120℃ to 380℃ for 30 to 40 hours; the sintering process involves sintering at a temperature of 1000℃ to 1450℃ for 4 to 10 hours in a reducing atmosphere.
Citation Information
Patent Citations
Manufacturing method for low temperature co-fired ceramic circuit board
CN109905981A
Manufacturing method of low-cost semiconductor cooler
CN121692983A